Discussion on the Reform of Higher Vocational English Teaching Based on Computer Work Process Systematization. Issue 3 (February 2021) - Ji, Fan
Abstract: In the computer age, higher vocational English teaching should combine the application of computer technology according to the characteristics of the profession, and the professional ability, method ability and social ability required for employment after graduation, and carry out the teaching reform of combining work with study. Formulate English curriculum standards that integrate work and study, adopt the "six-step approach" in engineering teaching, implement "task-driven" teaching, and cultivate autonomous learning. Develop teaching resources that combine work and study, build online courses, provide an open teaching environment, ensure open learning time, open learning places, open learning environments, and open learning resources to comprehensively cultivate students' English quality and improve work skills.